2020
DOI: 10.1155/2020/6198628
|View full text |Cite
|
Sign up to set email alerts
|

PPARs and the Development of Type 1 Diabetes

Abstract: Peroxisome proliferator-activated receptors (PPARs) are a family of transcription factors with a key role in glucose and lipid metabolism. PPARs are expressed in many cell types including pancreatic beta cells and immune cells, where they regulate insulin secretion and T cell differentiation, respectively. Moreover, various PPAR agonists prevent diabetes in the non-obese diabetic (NOD) mouse model of type 1 diabetes. PPARs are thus of interest in type 1 diabetes (T1D) as they represent a novel approach targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 162 publications
0
17
0
1
Order By: Relevance
“…PPAR- α activation increases the expression of sirtuin-1 (SIRT1), which inhibits NF- κ B, depending on the AMPK pathway and thus reducing inflammation [ 38 , 39 ]. Dealing with hyperlipidemia, fenofibrate decreased TNF α and IFN- γ , but the levels had increased in PPAR α knockout mice [ 40 ]. It was reported that PPAR- α activation could decrease IR-induced liver, heart, and brain injury by suppressing inflammation, apoptosis, and lipid peroxidation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR- α activation increases the expression of sirtuin-1 (SIRT1), which inhibits NF- κ B, depending on the AMPK pathway and thus reducing inflammation [ 38 , 39 ]. Dealing with hyperlipidemia, fenofibrate decreased TNF α and IFN- γ , but the levels had increased in PPAR α knockout mice [ 40 ]. It was reported that PPAR- α activation could decrease IR-induced liver, heart, and brain injury by suppressing inflammation, apoptosis, and lipid peroxidation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor alpha (PPARA) is a ligand-activated transcription factor that belongs to the nuclear hormone receptor superfamily [ 15 , 16 ]. Studies have demonstrated that PPARA plays a critical role in lipid metabolism and the inflammatory response [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, many neurodegenerative diseases are listed, and diabetes mellitus is widely known to be a risk factor for neurodegenerative diseases [8][9][10][11][12]. Moreover, diabetes mellitus is known to be associated with thermogenesis [13], oxidative phosphorylation [14], and the PPAR signaling pathway [15]. Thus, the proposed method is successful in contrast to the first impression and can identify many diseases associated with diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%